BAY’ AL-WAFA’: PERMASALAHAN DAN SOLUSI DALAM IMPLEMENTASINYA - Sri Sudiarti (Program Pascasarjana UIN Sumatera Utara, 2016)
Contract Bay al-Wafa’ is one form of sale and purchase agreement that emerged in the mid-fifth century AH in Central Asia (Bukhara and Balk). Contract bay al-wafa' is a conditional sale and purchase, where goods that have been sold can be bought back by the seller at the same price. This study used a qualitative approach with in-depth interviews as the main instrument for data collection. This study took place in three districts, namely North Labuhan Batu district, Madina and Serdang Berdagai district. The cause of the emergence of the practice of contract bay al-Wafa’ among the people of North Sumatra due to: the needs of society to meet the needs of families and their survival and continuation of education, transactions carried out by the public by using of bay al-wafa' is a perceived risk of business activities lighter., very helpful and useful and the process is very simple, easy and quick to be realized, and the practice of contract bay al-wafa' in North Sumatra have a different names they use, but the form of what they do and goals to be achieved are the same, there are three terms that are found in the life of society, namely: Taxation, Pagang Pawn and Sell Pawn. The form of practice is likened to someone who needs money / funds for the needs of children's school fees or other needs in the family, they sell / pawn their farms, rice fields or their yards to get costs / funds, with the agreement if the funds obtained had been able to be restored, the farms, rice fields or the yards that serve as the object of transaction returned to the proprietor owner of farms, rice fields or yards. During the time the money can not be returned by the owner of the farms, rice fields or yards as long as it also the buyer or recipient had been able to take benefit from the land. What do these people seemed okay by them due to the lack of gharar factor or deception among them, instead they have been helped and easier their problem, by that the walfare is creted and refuse the badness in their lives, this is what required by Islamic law. Can not be denied that 'urf or culture instrumental fills a legal vacuum that never exist in al-Quran and the Sunnah of the Prophet, especially related to muamalah, contract bay al-wafa' is a form of transaction that is anchored in the istihsan 'urfy.